Analysis of squeeze flow of fluids between solid and porous surfaces. (January 2015) - Majhi, Akankshya; Pardhi, Tarun Kumar; Deshpande, Abhijit P.
Graphical abstract: Highlights: Model fluids and fabrics, that are used in composite industry, were used to study the squeeze flow. Experimental results for squeeze flow between solid surfaces follow Stefan equation. Models based on slip and permeability were used to analyse the squeeze flow between a porous surface and a solid surface. Model parameters were used to understand the behaviour of different fluid–fabric combinations. Abstract: Squeeze flow of fluids between surfaces is important in rheology, material processing, lubrication and biomedical applications. The surfaces for squeezing can be solid and/or porous. In this work, the squeeze flow between a porous surface and a solid surface is examined with Newtonian model fluids and model fabrics used in composite processing. Given that the fluid is expected to impregnate the fabric, the permeability and the wettability of the fluid–fabric combination are of utmost importance. Constant velocity squeeze flow experiments were carried out with polyester and polyol resins, while glass fabrics with different sizings were used as the porous surfaces. To understand the variation of the normal force during squeeze flow, its scaling with squeeze gap is evaluated. The scaling is observed to vary from −3 to −1 for different squeeze flow experiments. Squeeze flow theories are used to examine the normal force variation for different fluid–fabric combinations. It is shown that a slip based squeeze flow model and a permeability based squeeze flow model can be used to understand the wettability and the permeability of a fabric with a specific fluid.